Thermo‐sensitive mitochondrial trifunctional protein deficiency presenting with episodic myopathy. Issue 4 (5th May 2022) - Schwantje, Marit; Ebberink, Merel S.; Doolaard, Mirjam; Ruiter, Jos P. N.; Fuchs, Sabine A.; Darin, Niklas; Hedberg‐Oldfors, Carola; Régal, Luc; Donker Kaat, Laura; Huidekoper, Hidde H.; Olpin, Simon; Cole, Duncan; et al.
Abstract: Mitochondrial trifunctional protein (MTP) is involved in long‐chain fatty acid β‐oxidation (lcFAO). Deficiency of one or more of the enzyme activities as catalyzed by MTP causes generalized MTP deficiency (MTPD), long‐chain hydroxyacyl‐CoA dehydrogenase deficiency (LCHADD), or long‐chain ketoacyl‐CoA thiolase deficiency (LCKATD). When genetic variants result in thermo‐sensitive enzymes, increased body temperature (e.g. fever) can reduce enzyme activity and be a risk factor for clinical decompensation. This is the first description of five patients with a thermo‐sensitive MTP deficiency. Clinical and genetic information was obtained from clinical files. Measurement of LCHAD and LCKAT activities, lcFAO‐flux studies and palmitate loading tests were performed in skin fibroblasts cultured at 37°C and 40°C. In all patients (four MTPD, one LCKATD), disease manifested during childhood (manifestation age: 2–10 years) with myopathic symptoms triggered by fever or exercise. In four patients, signs of retinopathy or neuropathy were present. Plasma long‐chain acylcarnitines were normal or slightly increased. HADHB variants were identified (at age: 6–18 years) by whole exome sequencing or gene panel analyses. At 37°C, LCHAD and LCKAT activities were mildly impaired and lcFAO‐fluxes were normal. Remarkably, enzyme activities and lcFAO‐fluxes were markedly diminished at 40°C. Preventive (dietary) measures improved symptoms for most. In conclusion, all patients with thermo‐sensitive MTP deficiency had a long diagnostic trajectory and both genetic and enzymatic testing were required for diagnosis. The frequent absence of characteristic acylcarnitine abnormalities poses a risk for a diagnostic delay. Given the positive treatment effects, upfront genetic screening may be beneficial to enhance early recognition.